Lateral and Medial Musculatures of Pelvic Limbs in Dogs - Normal Ultrasonographic Anatomy - Carneiro, Rafael Kretzer [UNESP]; Kniphoff da Cruz, Igor Cezar [UNESP]; Lima, Bruna [UNESP]; Goncalves Neto, Jose Aloizio [UNESP]; Gasser, Beatriz [UNESP]; Ramirez Uscategui, Ricardo Andres; Bortoluzzi, Eduarda Mazzardo; Nogueira Aires, Luiz Paulo [UNESP]; Minto, Bruno Watanabe [UNESP]; Rossi Feliciano, Marcus Antonio (Univ Fed Rio Grande Do Sul, 2022)
Background: Pelvic limb claudication is a common problem in dogs. However, determining the location of the lesion can be challenging. Diagnostic imaging is essential for identifying and evaluating muscle injuries. Ultrasonographic evaluation is frequently performed to identify muscle injuries. Although some muscle changes have already been described as ultrasonography findings in veterinary studies, little is known about the standardization of these muscle structures, especially in hip muscles. The objective of this study was to describe the normal ultrasound anatomy of the lateral and medial muscles of the pelvic limb and establish an unprecedented protocol for the evaluation of these structures. Materials, Methods & Results: A total of 4 lateral and 4 medial musculatures of the pelvic limb of dogs were evaluated using ultrasound. An initial ex vivo study (1st phase) was performed to delineate anatomical and ultrasonographic assessments. The 2nd experimental phase proceeded with the application of in vivo scanning. The same operator performed all anatomical and ultrasonographic assessments. The gluteus medius, vastus lateralis, tensor fasciae latae, sartorius, pectineus, gracilis, adductor, and rectus femoris muscles were evaluated in longitudinal and transverse planes. Ten paired hips from 5 cadavers consisting of 3 females (60%) and 2 males (40%) were evaluated during the ex vivo phase. The average age and weight of the dogs were 3.6 +/- 0.87 years and 21.9 +/- 5.2 kg, respectively. The in vivo study included 4 females (40%) and 6 males (60%), for a total of 10 healthy animals consisting of 20 hips; the mean weight was 30.11 +/- 7.45 kg and the average age was 4.5 +/- 2.75 years. All muscles maintained the same ultrasound pattern when compared with each other and between different groups in the in vivo study. The longitudinal section presented a hypoechoic structure permeated by thin hyperechoic longitudinal striations. The hypoechoic aspect was maintained, with striae identified as hyperechogenic points in the cross-sectional view. Discussion: B-mode ultrasonographic evaluation with a high-frequency transducer has facilitated the identification of the lateral and medial muscles of the pelvic limbs of medium and large dogs ex vivo and in vivo. This approach is an effective and safe way to access these muscles, and aids in the establishment of an unprecedented protocol for ultrasound evaluation of this region. Understanding the normal ultrasonographic anatomy is essential to identify muscle injuries such as contractures, tumors, ruptures, and stretch, which can lead to loss of muscle echogenicity and echotexture. Furthermore, ultrasound standardization reduces inter-observer error, facilitates technique reproducibility, assists in a more assertive assessment, and directs the patient's most appropriate therapy. In addition, anatomical dissection with the aid of acoustic gel injection into the evaluated musculature is essential to guide the examination because it allows the confirmation of the structures. In this study, the ultrasound scans of 6 fundamental muscles (gluteus medius, tensor fasciae latae, gracilis, adductor, pectineus, and rectus femoris) for hip mobility and 2 knee muscles (sartorius and vastus lateralis) were standardized. Ex vivo evaluations facilitated the application of in vivo techniques, and no difficulties were found during these evaluations.
Keywords: canine; fundamental muscles; imaging; diagnosis; ultrasound; neoplasm